STRENGTHENING THE FOOD SECURITY OF UZBEKISTAN THROUGH THE DEVELOPMENT OF AGRO-INDUSTRIAL INTEGRATION (Innovative Technologica: Methodical Research Journal, 2023)
In the article the importance of agro-industrial integration in ensuring the food security of the Republic of Uzbekistan and the issues of improving the organizational and economic mechanisms for the development of integration structures in the field of production and processing of agricultural products are considered.